Simvastatin Evokes An Unpredicted Antagonism For Tamoxifen In MCF-7 Breast Cancer Cells - Ibrahim AB; Zaki HF; Wadie W; Omran MM; Shouman SA (Cancer Management and Research, 2019)
Amel B Ibrahim,1 Hala F Zaki,2 Walaa Wadie,2 Mervat M Omran,3 Samia A Shouman3 1Department of Pharmacology, Faculty of Medicine, Zawia University, Zawiya, Libya; 2Department of Pharmacology and Toxicology, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 3Department of Cancer Biology, Pharmacology Unit, National Cancer Institute, Cairo University, Cairo 11796, EgyptCorrespondence: Samia A ShoumanDepartment of Cancer Biology, National Cancer Institute, Cairo University, Kasr Al Eini Street, Fom El Khalig, Cairo 11796, EgyptFax +202-23644720Email samia.shouman@nci.cu.edu.egPurpose: Tamoxifen (TAM) is a non-steroidal antiestrogen drug, used in the prevention and treatment of all stages of hormone-responsive breast cancer. Simvastatin (SIM) is a lipid-lowering agent and has been shown to inhibit cancer cell growth. The study aimed to investigate the effect of the combination of TAM and SIM in the treatment of estrogen receptor positive (ER+) breast cancer cell line, MCF-7, and in mice-bearing Ehrlich solid tumors.Methods: MCF-7 cells were treated with different concentrations of TAM or/and SIM for 72 hours and the effects of the combination treatment on cytotoxicity, oxidative stress markers, apoptosis, angiogenesis, and metastasis were investigated using different techniques. In addition, tumor volume, oxidative markers, and inflammatory markers of the combined therapy were explored in mice bearing solid EAC tumors.Results: The results showed that treatment of MCF-7 cells with the combination of 10 μM TAM, and 2 μM SIM significantly inhibited the increase in oxidative stress markers, LDH, and NF-kB induced by TAM. In addition, there was a significant decrease in the total apoptotic ratio, caspase-3 activity, and glucose uptake, while there was a non-significant change in Bax/bcl-2 ratio compared to the TAM-treated group. Using the isobologram equation, the drug interaction was antagonistic with combination index, CI=1.18. On the other hand, the combination regimen decreased VEGF, and matrix metalloproteinases, MMP 2&9 compared to TAM-treated cells. Additionally, in vivo, the combination regimen resulted in a non-significant decrease in the tumor volume, decreased oxidative markers, and the protein expression of TNF-α, and NF-κB compared to the TAM treated group.Conclusion: Although the combination regimen of TAM and SIM showed an antagonistic drug interaction in MCF-7 breast cancer, it displayed favorable antiangiogenic, anti-metastatic, and anti-inflammatory effects.Keywords: combined therapy, antitumor effect, apoptosis, oxidative markers, VEGF